Genetic Variations and mRNA Expression of NRF2 in Parkinson's Disease. (2nd May 2017) - Ran, Caroline; Wirdefeldt, Karin; Brodin, Lovisa; Ramezani, Mehrafarin; Westerlund, Marie; Xiang, Fengqing; Anvret, Anna; Willows, Thomas; Sydow, Olof; Johansson, Anders; Galter, Dagmar; Svenningsson, Per; et al.
Abstract : Nuclear factor erythroid 2-like 2 (NRF2) encodes a transcription factor regulating mechanisms of cellular protection and is activated by oxidative stress. NRF2 has therefore been hypothesized to confer protection against Parkinson's disease and so far an NRF2 haplotype has been reported to decrease the risk of developing disease and delay disease onset. Also NRF2 adopts a nuclear localization in Parkinson's disease, which is indicative of increased NRF2 activity. We have investigated the association between NRF2 and Parkinson's disease in a Swedish case-control material and whether NRF2 expression levels correlate with NRF2 genetic variants, disease, or disease onset. Using pyrosequencing, we genotyped one intronic and three promoter variants in 504 patients and 509 control subjects from Stockholm. Further, we quantified NRF2 mRNA expression in EBV transfected human lymphocytes from patients and controls using quantitative real-time reverse transcription PCR. We found that one of the promoter variants, rs35652124, was associated with age of disease onset (Χ 2 = 14.19, p value = 0.0067). NRF2 mRNA expression levels however did not correlate with the rs35652124 genotype, Parkinson's disease, or age of onset in our material. More detailed studies on NRF2 are needed in order to elucidate how this gene affects pathophysiology of Parkinson's disease.